Analysis of College Students’ Conceptual Understanding on Work and Energy Topic in Various Representations - Firmansyah, Danny; Muhammad Reyza Arief Taqwa; Setiyani, Amira; Intan Ramadani, Cahyani (Department of Physics Education, Universitas Mataram, 2023)
The study aims to determine students' conceptual understanding of work and energy in various representations. The research method used in this study is a mixed method with a sequential explanatory design. The data in this study were quantitative data and qualitative data. Quantitative data analysis was performed using descriptive statistics. The research subjects consisted of 45 physics students at Universitas Negeri Malang who had taken the fundamental of physics course I. In this study, 10 multiple choice questions were used on the work and energy topic presented in various representations. The results showed that the understanding of concepts in the work and energy topic in various representations was still relatively low, which was indicated by the average score of students only reaching 42.22. The lowest concept of understanding occurs in the sub-material of work and kinetic energy, which is presented in a mathematical representation. Some of the errors experienced by students in the concept of work include: (1) students assume that gravity is the same as the tensile force on the block, (2) work is an ordinary product of force and displacement, and (3) do not pay attention to the meaning of the multiplication symbol between vector quantities. While in the concept of kinetic energy, the errors experienced include: (1) students use equations in the form of conclusions without starting from the variables raised in the problem and (2) assume that kinetic energy is only influenced by mass, so that they do not consider the speed of the two objects.